EnglishDAMPAK UJIAN LISAN TERSTRUKTUR TERHADAP PROSES BELAJAR MAHASISWA: PENELITIAN KUALITATIF DI FAKULTAS KEDOKTERAN UNIVERSITAS JENDERAL SOEDIRMAN - Miko Ferine; Rizkia Nauvalina; Diyah Woro Dwi Lestari (Fakultas Kedokteran Universitas Jenderal Soedirman, 2023)
The oral examination is one of the traditional assessment methods which is considered to have low validity and reliability. However, several medical schools in Indonesia use structured oral examination as a part of the assessment systems, such as faculty of medicine Universitas Jenderal Soedirman. Structured oral examination is expected to have positive impact on student learning motivation. This research was conducted to explore students’ perception on the impact of structured oral examination on their learning. The research was a qualitative research with phenomenology approach. In-depth interviews were conducted with 5 students who were selected based on different gender and year of study. The results of this research indicated that students were motivated to learn better for structured oral examination since they had to face the examiner directly, they should understand the learning material in order to be able to do the examination and they must present the answers in a structured manner so that the examiner understood them. The issue of subjectivity became one of the triggers for students to study better. The methods used by students in preparing for structured oral examination were attending lectures and group discussions well, studying in groups and using audiovisual media to increase understanding. The negative impact of structured oral examination was the anxiety that arouse when students were about to take the examination. The large number of possible materials to be tested caused students to lose their focus on learning. Students realized that they should have good preparation to take the structured oral examination. Based on the results, it could be concluded that structured oral examination had a more positive impact than negative impact on student learning process. Keywords: learning impact, medical education, oral examination, structured oral examination